2019
DOI: 10.1093/nar/gkz1052
|View full text |Cite
|
Sign up to set email alerts
|

DSS1 interacts with and stimulates RAD52 to promote the repair of DSBs

Abstract: The proper repair of deleterious DNA lesions such as double strand breaks prevents genomic instability and carcinogenesis. In yeast, the Rad52 protein mediates DSB repair via homologous recombination. In mammalian cells, despite the presence of the RAD52 protein, the tumour suppressor protein BRCA2 acts as the predominant mediator during homologous recombination. For decades, it has been believed that the RAD52 protein played only a back-up role in the repair of DSBs performing an error-prone single strand ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 73 publications
5
26
0
Order By: Relevance
“…DSS1 was found to act as a DNA mimic, displacing RPA to allow BRCA2 binding to ssDNA ( 28 ). Recently, an unexpected interaction between RAD52 and DSS1 was discovered, which also modulates RAD52 oligomeric state and increases its DNA binding and single strand annealing activities ( 53 ). In this new role, DSS1 does not function as a DNA mimic and independent of RPA ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSS1 was found to act as a DNA mimic, displacing RPA to allow BRCA2 binding to ssDNA ( 28 ). Recently, an unexpected interaction between RAD52 and DSS1 was discovered, which also modulates RAD52 oligomeric state and increases its DNA binding and single strand annealing activities ( 53 ). In this new role, DSS1 does not function as a DNA mimic and independent of RPA ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an unexpected interaction between RAD52 and DSS1 was discovered, which also modulates RAD52 oligomeric state and increases its DNA binding and single strand annealing activities ( 53 ). In this new role, DSS1 does not function as a DNA mimic and independent of RPA ( 53 ). Our experiments were conducted in the absence of RPA, and the synergistic manner by which DSS1 blocks BRCA2 self-association in conjunction with ssDNA suggests an additional function of DSS1 besides acting as a DNA mimic.…”
Section: Discussionmentioning
confidence: 99%
“…Stefanovie et al established another important contributor to DSBR. A small, acidic protein called DSS was shown to play a crucial role in stimulation of RAD52 oligomer formation and consequent strand invasion during single-strand annealing (SSA) and break-induced replication (BIR) repair processes [172]. Moreover, new emerging functions of RAD52 in DNA repair have been proposed by Jalan et al [173].…”
Section: Other Playersmentioning
confidence: 99%
“…Similarly, RAD52 interaction with specific partners is expected to modulate its repair function. It has been very recently reported that association of RAD52 with DSS1 can promote BIR in cell models [59]. RAD51AP1 also interacts with RAD52 and facilitates its recruitment to telomeres during ALT [60].…”
Section: Regulation Of Rad52 and Its Relevance In Dsb Repairmentioning
confidence: 98%
“…Under these conditions, RAD52 has been shown to perform roles either downstream or upstream DSBs formation [45,82,102]. Several works in the last years supported or reported a function for RAD52 in the repair of collapsed replication forks by BIR [45,47,59,109,110]. In yeast, the relevance of Rad52 for BIR have been vastly demonstrated over the years as well as it has been shown that Rad52 participates to both Rad51-dependent and independent BIR [42].…”
Section: Rad52 As a Partner Of Mus81mentioning
confidence: 99%